"Uplifting the Nation": Karola Gajda's Are My Roots Showing? as a Modified Practice of "the New Behalfism" - Bartnik, Ryszard (My University, 2025)
Along with Benedict Anderson’s formulation of the concept of ‘imagined communities’, a new interest in questions concerning representations of national identities could be observed. An important notion to be addressed is how/to what degree various representatives of a specific literary field were/are willing to contribute to that kind of debates. Of some interest, in the above context, would be to observe the inscriptions and imagery used by the novelists of referential fiction that run parallel to certain ‘mythmaking’ projections of a given nationhood, constructed often at the expense of more adequate depictions of national identity. With this in mind, the following paper presents a socio-cultural critique of one such writer, namely Karola Gajda. Studying her novel Are My Roots Showing?, I examine how adequate her reasoning and the ways she [re]imagined contemporary Poland as well as its collective mindset are.
Keywords: Polish identity; myth-making narratives; Polish diaspora and literature; nationhood